Анализа упоредбе нивоа ЛДХ, β2-МГ, ИЛ-2Р и ИЛ-10 у серуму код пацијената са лимфомом: Нивои серума ЛДХ, β2-МГ, ИЛ-2Р и ИЛ-10 код пацијената са лимфомом - Xu, Xifeng; Wen, Yilin; Yao, Rongquan; Zhang, Jianping (Journal of Medical Biochemistry, 2026)
[Objective] To investigate the variations and clinical relevance of blood levels of β2-microglobulin (β2-MG), interleukin (IL)-2R, IL-10, and lactate dehydrogenase (LDH) in patients with lymphoma who have various circumstances. [Methods] A total of 200 lymphoma patients diagnosed in this hospital from 2021–2025 were selected as the lymphoma group. Serum samples and data such as age, sex, lymphoma tissue, immunological type, clinical stage, bone marrow infiltration, and Epstein–Barr virus (EBV) infection were collected. During the same period, serum samples and data from 80 healthy individuals who underwent physical examinations (the control group) were collected. The levels of serum LDH, β2-MG, IL-2R and IL-10. Changes in the levels of each index in lymphoma tissue, tissue immunological type, clinical stage, bone marrow infiltration, and Epstein–Barr virus (EBV) infection and after effective treatment were analyzed. [Results] The lymphoma group had greater levels of serum LDH, β2-MG, IL-2R, and IL-10 than the control group (P<0.05). Serum LDH, β2-MG, and IL-2R levels were higher in EBV+ patients than in EBV-patients (P<0.05). Patients with clinical stage III–IV disease and bone marrow infiltration had higher serum levels of LDH, β2-MG, and IL-2R as the disease progressed compared to those with clinical stage Ⅰ–II disease without bone marrow infiltration (P<0.05). Patients with lymphoma had lower serum levels of β2-MG, IL-2R, IL-10, and LDH after treatment than they had before. [Conclusion] Monitoring the changes in the serum levels of LDH, β2-MG, IL-2R and IL-10 has important clinical value for the auxiliary diagnosis of lymphoma patients, EBV infection, clinical staging, therapeutic effects and prognostic evaluation.